CaO ADSORBENT FOR REDUCING METAL CONTENT OF Fe, Mn, AND Zn FROM PET-SET WASTE-WATER - Jefri Jefri; Siti Rodiah (Jambura Journal of Health Sciences and Research, 2022)
Primary Effluent Treatment-Secondary Effluent Treatment (PET-SET) is refinery waste-water. PET-SET waste contains hazardous substances, namely Fe, Mn and Zn metal ions. The novelty of this research is that it looks at the CaO adsorbent to reduce the metal content of Fe, Mn, and Zn from PET-SET Waste-water. This research's aimed to reduce the metal content of Fe, Mn, and Zn using CaO adsorbent. CaO was prepared from the golden snail shell by previous researchers. Concentration of Fe, Mn, and Zn from PET-SET waste before treatment were 8.6 mg/L, 8.52 mg/L and 9.28 mg/L. This research was conducted through the adsorption method by variating the adsorbent mass and contact time to determine the optimum condition in the absorption of Fe, Mn, and Zn metal ions that analyzed using the ICP-OES instrument. This instrument was quite well used for multielement analysis. In this study, CaO was applied to adsorb previously treated PET-SET waste samples which previous reasearcher used CaO from golden snail shell as a catalyst for transesterification reaction. It was reported that the optimum condition to absorb Fe, Mn, and Zn metal ions was 0.2 g for 20 minutes with an absorption effectiveness of 100% .